2020
DOI: 10.3390/genes11091065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNMT3B2 as the Predominant Isoform of DNMT3B in Porcine Alveolar Macrophages and Its Involvement in LPS-Stimulated TNF-α Expression

Abstract: DNA methyltransferase 3B (DNMT3B) as one member of the DNMT family functions as a de novo methyltransferase, characterized as more than 30 splice variants in humans and mice. However, the expression patterns of DNMT3B in pig as well as the biological function of porcine DNMT3B remain to be determined. In this study, we first examined the expression patterns of DNMT3B in porcine alveolar macrophages (PAM). We demonstrated that only DNMT3B2 and DNMT3B3 were the detectable isoforms in PAM. Furthermore, we reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We are particularly interested in the role of epigenetic regulation by DNA methylation in the immune response of porcine macrophages. In a previous study, we identified DNMT3B2 as the predominant isoform of DNMT3B in porcine alveolar macrophages and demonstrated its potential role in the regulation of lipopolysaccharide (LPS)-stimulated tumor necrosis factor α (TNF-α) expression [26]. In this study, we characterized DNMT1 in porcine alveolar macrophages.…”
Section: Introductionmentioning
confidence: 88%
“…We are particularly interested in the role of epigenetic regulation by DNA methylation in the immune response of porcine macrophages. In a previous study, we identified DNMT3B2 as the predominant isoform of DNMT3B in porcine alveolar macrophages and demonstrated its potential role in the regulation of lipopolysaccharide (LPS)-stimulated tumor necrosis factor α (TNF-α) expression [26]. In this study, we characterized DNMT1 in porcine alveolar macrophages.…”
Section: Introductionmentioning
confidence: 88%
“…RAW264.7 cells (ATCC) were maintained in Dulbecco’s modified Eagle medium (DMEM) with high glucose (Gibco, Invitrogen Corp., Carlsbad, CA, USA) supplemented by 10% (vol/vol) heat-inactivated fetal bovine serum (FBS) (Invitrogen). Porcine alveolar macrophages (PAMs) were isolated from piglets as previously described and cultured in RPMI 1640 containing 10% FBS, penicillin, streptomycin, and GlutaMAX (all purchased from Thermo Fisher Scientific, Shanghai, China) at 37 °C with 5% CO 2 [ 27 ]. For cell stimulation, RAW264.7 cells and PAMs were grown in 12-well tissue culture plates at a concentration of 4 × 10 5 cells/well.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to wild-type mice, Tet2-deficient mice are more susceptible to endotoxic shock and dextran sulfate sodium-induced colitis, leading to aggravated inflammation and IL-6 storm [227] (Figure 6C). In addition, during the polarization process of porcine macrophages stimulated by LPS, the expression of DNTM3b is reduced, leading to a downregulation of the methylation level of the Tnf-α gene promoter, thereby promoting its transcription [228] . Similarly, porcine reproductive and respiratory syndrome virus (PRRSV) infection in porcine macrophages inhibits the expression of FTO, resulting in an increase in m 6 A methylation levels.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%